Old English geond expressing duration of time: The Winchester usage - Sato, Kiriki (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
“The Winchester group” is a restricted group of late Old English texts, including the works of Ælfric, which are connected with Winchester. They are known to show a remarkable uniformity in their choice of vocabulary within certain groups of synonyms. Lexical studies confi rm the existence of “Winchester words”—the Winchester group’s preferred words (Gneuss 1972, Ono 1986, Hofstetter 1987 & 1988, Gretsch 2001). However, no study has considered the possibility that the Winchester group may show syntactic uniformity as well. In this article, I focus on the preposition geond ‘through, throughout’, used to express duration of time. In the Old English period, the adverbial accusative was commonly used for this function. In fact, temporal prepositions were not yet fully developed, and geond was rarely employed as such. Utilizing the Dictionary of Old English Corpus, I will demonstrate that the use of the temporal geond is strictly confi ned to the Winchester group. Keywords: Ælfric, duration of time, geond, Old English, temporal preposition, the Winchester group.